Unpacking the concept of political will to confront corruption - and Brinkerhoff, Derek W. (U4 Anti-Corruption Resource Centre, 2010)
Quite often, "lack of political will" is identified as the culprit for poorly performing anti-corruption programmes. Yet despite the frequency with which it is used to explain unsatisfactory reform outcomes, political will remains under-defined and poorly understood. Further, assessments are often conducted retrospectively, looking back at failed programmes. By applying a model of political will that specifies a set of action-based components that are observable and measurable, and amenable to external reinforcement and support, more clarity regarding the degree of political will can be achieved.